Timing resistance training. Programming the muscle clock for optimal performance - Ashmore, A. (Human Kinetics, 2020)
Since periodization training`s emergence in the 1950s, sport scientists have known that timing is one of the most critical programming variables influencing peak athletic performance. Modern research has taken the application of timing to exercise programming in a new direction, discovering the existence of time clocks inside each of the more than 600 skeletal muscles. Timing Resistance Training examines how these internal clocks use cues provided through exercise programming to regulate physiological processes for better performance.